INCREASING TECHNOLOGY, INFORMATION AND COMMUNICATION (ICT) LITERACY THROUGH STRENGTHENING VISIONARY LEADERSHIP, WORK-LIFE BALANCE, TRAINING EFFECTIVENESS AND ACHIEVEMENT MOTIVATION - Suhendri, Huri; Retnowati, Rita; Sumaryoto, Sumaryoto (Yayasan Education and Social Center, 2024)
This research aims to determine the increase in technology, information and communication (ICT) literacy through strengthening visionary leadership, work-life balance, training effectiveness and achievement motivation. The research was carried out at a private vocational school in the city of South Jakarta. The research method used is a survey method with hypothesis testing using path analysis. The population in this study was 186 private vocational school mathematics teachers in the city of South Jakarta and the research sample was 127 people and the sample was taken using a proportional stratified random sampling technique. The research results show that: (1) there is a significant direct positive influence of visionary leadership on ICT literacy; (2) there is a significant direct positive influence of work-life balance on ICT literacy; (3) there is a significant direct positive effect of training effectiveness on ICT literacy; (4) there is a significant direct positive influence of achievement motivation on ICT literacy; (5) there is a direct influence of visionary leadership on achievement motivation, (6) there is a direct influence of work-life balance on achievement motivation, (7) there is a direct influence of training effectiveness on achievement motivation, (8) there is an insignificant positive indirect effect of visionary leadership on ICT literacy through achievement motivation; (9) there is an indirect and insignificant positive influence of work-life balance on ICT literacy through achievement motivation; and (10) there is a positive indirect influence that is not significant on the effectiveness of training on ICT literacy through achievement motivation